THE EFFECT OF LEAD (Pb) LEVELS IN THE BLOOD ON HEMOGLOBIN (Hb) LEVELS IN BOOK PRINTING PERSONNEL ON JALAN KARAH SURABAYA - Ursula Yesi Gusti Ayuputri; Soedjajadi Keman (The Indonesian Journal of Public Health, 2021)
Lead (Pb) is a metal used as raw material for color pigments in printing ink. Pb exposure caused by printing ink can cause an increase in Pb levels in the blood and a decrease in hemoglobin levels. This study aimed to analyze the effect of Pb levels of ink on Pb levels in blood, as well as the effect of Pb levels in the blood on hemoglobin levels in book printing employees on Jalan Karah Surabaya. This study included analytic observational research, the research design used was the cross-sectional design, and the multiple linear correlation test was used for analysis. The results showed that the Pb level in ink had an effect on the Pb level in the blood (p = 0.000; OR = 0.762). The employee characteristics, namely work period, had an effect on Pb level in blood (p = 0.000; OR = 0.883). Age, use of Personal Protective Equipment (PPE) and personal hygiene do not affect the Pb level in the blood. Pb levels in the blood affect blood hemoglobin levels (p = 0.001; OR = -0.724). Employee characteristics, namely their work period, affect blood hemoglobin levels (p = 0.046; OR = -0.4471). Age and nutritional status did not affect the blood hemoglobin level. The conclusion in this study is that Pb levels in ink increases Pb levels in the blood, and Pb levels in the blood decrease blood hemoglobin levels. Therefore, it is necessary to monitor lead levels in the blood by periodic examination every 6 or 12 months. Book printing personnel should also take supplements containing calcium, iron (Fe), and vitamin C to inhibit lead absorption.Keywords: Pb levels in ink, blood Pb levels, Hb levels, printing employees.